Gambaran pelaksanaan administrasi pelayanan kesehatan di Puskesmas - Nurhayati, Nurhayati; Najwa, Aqila; Nasution, Putri Suci Khoirunnisa; Salsabila, Salsabila; Fadhillah, Naya Kurnia; Andriani, Riri; Salsabilah, Khairani; Khaiyath, Salsabilla Aishya (Indonesian Public Health-Observer Information Forum (IPHORR) Kerja sama dengan: Unit Penelitian dan Pengabdian Kep Akademi Keperawatan Baitul Hikmah, 2026)
Background: Primary health care is the main foundation of the health system and requires effective administrative support to ensure continuity, quality, and efficiency of services. Community health centers (Puskesmas) as first-level health facilities have a strategic role in the provision of health services, including in the management of service administration. However, limited facilities, infrastructure, and information systems remain a challenge in the implementation of health service administration at the Puskesmas level. Purpose: To describe the implementation of health service administration at Puskesmas and identify obstacles as an effort to support smooth service delivery. Method: The study was conducted at the Mampang Community Health Center, South Labuhan Batu Regency on December 19, 2025. This study involved three administrative officers who met the criteria and had responsibilities as health service administrators at the Community Health Center. The sample was selected purposively by considering their experience and active involvement in the service administration process. This study applied a qualitative approach with a descriptive design to explain how health service administration is carried out at the Community Health Center. Information was collected through in-depth interviews using a semi-structured interview guide. The analysis process was carried out repeatedly to ensure that data interpretation remained consistent and in accordance with established guidelines. The results of the analysis are presented in the form of a narrative that describes the implementation of health service administration at the Mampang Community Health Center. Results: Healthcare services include serving an average of 12 patients per day, preparing and administering medication, preparing referral letters, confirming and coordinating with referral providers. When the network is unstable, patients are asked to wait until the network returns to normal. Emergency patients are directed directly to the referral hospital, and staff continue to serve patients using manual recording to ensure uninterrupted service and input data after the system returns to normal. Administrative services include recording and documenting each stage of the activity, inputting data into a PC application, and archiving documents. Conclusion: This activity illustrates that healthcare administration activities have been carried out in accordance with established procedures, from patient registration to medication distribution. However, various challenges remain in the implementation of healthcare administration, particularly related to administrative equipment, internet networks, and communication media, which contribute to speed and accuracy of service delivery, thus optimizing service administration. Suggestion: The Mampang Community Health Center is expected to improve the facilities and infrastructure that support healthcare administration, particularly by adding computers and providing better internet connections. Furthermore, it is important to enhance the capabilities of human resources in the administrative field through training and skills development to ensure better and more efficient healthcare administration processes. Keywords: Community health center; Healthcare administration; Health management; Primary healthcare Pendahuluan: Pelayanan kesehatan primer merupakan fondasi utama dalam sistem kesehatan dan memerlukan dukungan administrasi pelayanan yang efektif untuk menjamin kesinambungan, mutu, dan efisiensi layanan. Puskesmas sebagai fasilitas kesehatan tingkat pertama memiliki peran strategis dalam penyelenggaraan pelayanan kesehatan, termasuk dalam pengelolaan administrasi pelayanan. Namun, keterbatasan sarana, prasarana, dan sistem informasi masih menjadi tantangan dalam pelaksanaan administrasi pelayanan kesehatan di tingkat Puskesmas. Tujuan: Untuk menggambarkan pelaksanaan administrasi pelayanan kesehatan di Puskesmas dan mengidentifikasi kendalanya sebagai upaya mendukung kelancaran pelayanan. Metode: Kegiatan dilaksanakan di Puskesmas Mampang, Kabupaten Labuhan Batu Selatan pada tanggal 19 Desember 2025. Studi ini melibatkan 3 petugas administrasi yang memenuhi kriteria dan memiliki tanggung jawab sebagai administrasi pelayanan kesehatan di Puskesmas. Sampel dipilih secara purposive dengan mempertimbangkan pengalaman serta keterlibatan aktif mereka dalam proses administrasi pelayanan. Studi ini menerapkan pendekatan kualitatif dengan desain deskriptif untuk menjelaskan bagaimana administrasi pelayanan kesehatan dilaksanakan di Puskesmas. Pengumpulan informasi dilakukan melalui wawancara mendalam dengan menggunakan panduan wawancara yang bersifat semi-terstruktur. Proses analisis dilakukan secara berulang untuk memastikan bahwa interpretasi data tetap konsisten dan sesuai dengan panduan yang telah ditetapkan. Hasil analisis disajikan dalam bentuk narasi yang menggambarkan pelaksanaan administrasi pelayanan kesehatan di Puskesmas Mampang. Hasil: Kegiatan dalam pelayanan kesehatan meliputi melayani pasien rata-rata 12 orang per hari, menyiapkan dan memberikan obat kepada pasien, membuat surat rujukan, konfirmasi dan koordinasi dengan pihak rujukan. Tindakan ketika jaringan tidak stabil, pasien diminta menunggu hingga jaringan kembali normal, sedangkan pasien gawat darurat diarahkan langsung ke rumah sakit rujukan dan petugas tetap melayani pasien dengan pencatatan manual agar pelayanan tidak terhenti dan melakukan input data setelah sistem kembali normal. Sedangkan untuk pelayanan administrasi meliputi pencatatan dan dokumentasi setiap tahap kegiatan, menginput data ke aplikasi di PC, dan arsip dokumen Simpulan: Kegiatan ini memberikan gambaran kegiatan administrasi pelayanan kesehatan telah dilakukan sesuai dengan prosedur yang telah ditetapkan, mulai dari pendaftaran pasien hingga distribusi obat. Meskipun demikian, berbagai tantangan masih dihadapi dalam implementasi administrasi pelayanan kesehatan, terutama terkait dengan masalah peralatan administrasi, jaringan internet dan media komunikasi untuk mendapatkan kecepatan dan akurasi pelayanan, sehingga administrasi pelayanan menjadi optimal. Saran: Diharapkan kepada pihak Puskesmas Mampang untuk memperbaiki fasilitas dan infrastruktur yang mendukung administrasi layanan kesehatan, terutama dengan menambah perangkat komputer dan menyediakan koneksi internet yang lebih baik. Selain itu, penting untuk meningkatkan kapabilitas sumber daya manusia di bidang administrasi melalui pelatihan dan peningkatan keterampilan agar proses administrasi layanan kesehatan dapat berjalan dengan lebih baik dan efisien.